Bioengineering lungs: An overview of current methods, requirements, and challenges for constructing scaffolds - Shakir, Shahad; Hackett, Tillie Louise; Mostaço-Guidolin, Leila B. (Frontiers in Bioengineering and Biotechnology, 2022)
Chronic respiratory diseases remain a significant health burden worldwide. The only option for individuals with end-stage lung failure remains Lung Transplantation. However, suitable organ donor shortages and immune rejection following transplantation remain a challenge. Since alternative options are urgently required to increase tissue availability for lung transplantation, researchers have been exploring lung bioengineering extensively, to generate functional, transplantable organs and tissue. Additionally, the development of physiologically-relevant artificial tissue models for testing novel therapies also represents an important step toward finding a definite clinical solution for different chronic respiratory diseases. This mini-review aims to highlight some of the most common methodologies used in bioengineering lung scaffolds, as well as the benefits and disadvantages associated with each method in conjunction with the current areas of research devoted to solving some of these challenges in the area of lung bioengineering.